Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I was trying to teach myself some basic Lie theory, and I came across this statement on Mathworld, relating the commutator of a group, $\alpha\beta\alpha^{-1}\beta^{-1}$, to the commutator of its Lie algebra, $[A,B] = AB-BA$:

For instance, let $A$ and $B$ be square matrices, and let $\alpha(s)$ and $\beta(t)$ be paths in the Lie group of nonsingular matrices which satisfy $$\begin{align} \alpha(0)=\beta(0) &= I \\ \left.\frac{\partial\alpha}{\partial s}\right|_{s=0} &= A \\ \left.\frac{\partial\beta}{\partial s}\right|_{s=0} &= B,
\end{align}$$ then $$\left.\frac{\partial}{\partial s}\frac{\partial}{\partial t}\alpha(s)\beta(t)\alpha^{-1}(s)\beta^{-1}(t)\right|_{(s=0,t=0)}=2[A,B].$$

When I tried to derive this for myself, using the fact that $$\left.\frac{\partial\alpha^{-1}}{\partial s}\right|_{s=0} = \left.-\alpha^{-1}\frac{\partial\alpha}{\partial s}\alpha^{-1}\right|_{s=0} = -A,$$ I expanded the expression to get $$\left.\frac{\partial}{\partial s}\frac{\partial}{\partial t}\alpha\beta\alpha^{-1}\beta^{-1}\right|_{(s=0,t=0)}$$ $$=\left.\left( \frac{\partial\alpha}{\partial s}\frac{\partial\beta}{\partial t}\alpha^{-1}\beta^{-1} + \alpha\frac{\partial\beta}{\partial t}\frac{\partial\alpha^{-1}}{\partial s}\beta^{-1} + \frac{\partial\alpha}{\partial s}\beta\alpha^{-1}\frac{\partial\beta^{-1}}{\partial t} + \alpha\beta\frac{\partial\alpha^{-1}}{\partial s}\frac{\partial\beta^{-1}}{\partial t} \right)\right|_{(s=0,t=0)}$$ $$=AB - BA - AB + AB$$ $$=[A,B].$$

The difference is that the factor of 2 is missing. This seems to agree with the lecture notes I found on MIT OCW, which state (in Ch. 2, PDF 1) that if $X, Y \in \mathfrak{g}$,

$\exp(-tX)\exp(-tY)\exp(tX)\exp(tY) = \exp\{t^2[X,Y]+O(t^3)\}$.

Since this is not my area of expertise, I wanted to make sure I got things right before I contacted MathWorld about a typo. Have I done something wrong somewhere, or is the MathWorld statement actually an error?

share|improve this question
7  
Don't believe everything that Wolfram's minions tell you :-) –  Robin Chapman Oct 26 '10 at 18:33
3  
Ignoring terms of order 3 and higher, and inverting 1+X using the power series, (1+A)(1+B)(1-A+A^2)(1-B+B^2) = (1 + (A+B) + AB) (1 - (A+B) + (A^2 + AB + B^2)) = 1 - (A+B)^2 + AB + A^2 + AB + B^2 = 1 - (A^2 + AB + BA + B^2) + 2AB + A^2 + B^2 = 1 + AB - BA = 1 + [A,B]. So no factor of 2. –  T.. Oct 26 '10 at 18:36
    
@Robin, @T..: That's good to know! Do either of you want to post an answer so I can accept it? –  Rahul Oct 26 '10 at 21:50
    
P.S. I have sent MathWorld a message about this. –  Rahul Oct 27 '10 at 1:56
    
@Rahul: I saw your recent meta thread and, looking at your question postings, realized that this discussion might have been the intended example. I undeleted the answer which, after posting, seemed to fit better as a comment, being a short and basically single-bit YES or NO answer to a [verification-request]. –  T.. Nov 14 '10 at 20:04

1 Answer 1

up vote 1 down vote accepted

Ignoring terms of order 3 and higher, and inverting 1+X using the power series,

(1+A)(1+B)(1-A+A^2)(1-B+B^2) = (1 + (A+B) + AB) (1 - (A+B) + (A^2 + AB + B^2)) = 1 - (A+B)^2 + AB + A^2 + AB + B^2 = 1 - (A^2 + AB + BA + B^2) + 2AB + A^2 + B^2 = 1 + AB - BA
= 1 + [A,B]

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.